Family Planning and Contraceptive Methods - Seyrek, Sabriye Gamze; Çakıroğlu, Muhammet Mahmut; İncekara, Nazlı (Turkey Health Literacy Journal, 2021)
Family planning is that a couple have as many children as they can care for and whenever they want. Family planning plays an importantrole in preventing unintended pregnancies that make up about %50 percent of all pregnancies and decreasing abortion, curretage,maternal mortality rate, sexual transmitted diseases because of unintented pregnancy and improvement various subjects about mother, baby and public health like raising the socioeconomic level of society. % 50 percent of unintented pregnancies occur because ofincomplete and incorrect using of contraceptive methods and no contraceptive method is used in the remaining % 50 percent ofunintented pregnancies. So types of contraceptive methods, funtional mechanism and effectiveness of contraceptives and usage rate of contraceptives in community should be known well for effective family planning. Correct usage of contraceptive methods andtypes of contraceptives have significant role on effectiveness of the methods and these effects have been seen in different studies. Forexample some studies show that long acting reversible contraceprives like intrauterin devices and subdermal implants are more effectivein preventing unintented pregnancies. With the right choice and the correct using of contraceptives and the more knowledge about contraceptive methhods , better family and population planning can be done.
Keywords: Types of Contraception Methods, Effectiveness of Contraception, Family Planing and it’s Benefits.